Embodied Idolatry: A Critique of Christian Nationalism - Haden, Kyle (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
Embodied Idolatry: A Critique of Christian Nationalism is an examination of the effect of Christian nationalism on Christian practice in the United States. Kyle Edward Haden focuses on the mechanisms by which such beliefs become sedimented into the emotional, embodied structures of the church and the individual. Using a variety of disciplines, Haden thus identifies and highlights how such beliefs and practices are, in fact, idolatrous and inhabit an anti-Christian theological and ethical space. This book describes the formative process and mechanisms by which social and cultural values are acquired through imitation, by the individual and within ecclesial communities. As a constructive countermeasure, it investigates Jesus’s practice in his own social, cultural, political, religious, and economic context, and argues that Christian nationalism is a betrayal of Jesus’s teachings in light of his own practice of hospitality and table fellowship. This book thus calls Christians to conversion, putting loyalty to the kingdom of God over that of the nation.